Pengaruh Profitabilitas, Ukuran Perusahaan, Kebijakan Dividen, Leverage, Price Earnings Ratio, dan Kebijakan Hutang Terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2012 - 2014) - Noviliyan, noviliyan; , Dr. Zulfikar, SE, M.Si (2016)
This study aims to provide empirical evidence of influence: profitability, company size, dividend policy, leverage, price earning ratio, and debt policy affect the value of the company. The population of this research is all manufacturing companies listed on the Stock Exchange in 2012-2014. While the sample of this research is manufacturing companies listed on the Stock Exchange in 2012-2014. This research was conducted using secondary data. The population in this study were 18 companies listed on the Indonesian Stock Exchange (BEI) during 2012-2014. The analytical method used is multiple linear regression analysis by first doing a description of the data, a classic assumption test including normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, and hypothesis testing used was a significant test of the partial (Uji- t), significant test simultaneous (Test F), and adjusted R Square. The results of this study prove that vaiabel audit profitability and dividend policy that has a positive impact on corporate value, while variable firm size, leverage, price-earnings ratio and the debt policy has no significant effect on the value of the company at a manufacturing company in Indonesia Stock Exchange.